HAK ASASI MANUSIA (HAM) DALAM ISLAM: MENELUSURI KONSEP HAM DALAM PIAGAM MADINAH - Ridhatullah Assya'bani (STAI AL FALAH Banjarbaru, 2018)
Until now, the discussion about humanity or human rights is still being discussed in national and international forums. Islam as a religion which is essentially a rahmat lil-‘alamin certainly has its own concept, especially with regard to human rights. The presence of Islam in its essence is to elevate human dignity, wherein pre-Islam human beings are treated unnaturally like 'slaves' who haphazardly employ without regard to human aspects. The concept of humanity in the Islamic tradition was proven when the Prophet Muhammad and Muslims migrated from the city of Mecca to the city of Medina, at that time the population of Medina was very heterogeneous and gave birth to the Constitution of Medina. Therefore, the author tries to trace the principles of human rights contained in the Constitution of Medina. The principles include brotherhood, freedom, and equality. Keywords: Constitution of Medina, Islam, Human Rights.